(untitled) (Research, Society and Development, 2022)
In healthy mucous membranes, epithelial cells are strongly adhered to each other, but in the presence of inflammatory or neoplastic changes, they lose their cohesive strength. In this sense, exfoliative cytology allows the early diagnosis of malignant and premalignant epithelial lesions, as well as the diagnosis of infections, inflammations, and other diseases caused by genotoxics. This paper aims to identify morphological alterations in the epithelium of the oral mucosa, making a correlation with social habits, such as smoking, alcohol consumption and food, in academics and servants of the Universidade Federal de Rondônia. The research was experimental with a quanti-qualitative approach from 17 biological samples collected from the oral mucosa of volunteers. The collection technique was exfoliative cytology on the inner part of the cheeks. The slides stained by the Pap smear technique were analyzed by optical microscopy with the aid of morphometric software. Information on social behaviors was obtained through the semi-structured interview technique. Pearson’s product-moment correlation coefficient was the technique for evaluating the correlation between quantitative variables. There was a high frequency of cell atypia in participants who had habits of smoking, alcoholism, poor diet and constant medication. Smoking shows a strong relationship with the high degree of dysplasia (IV), including passive smokers in this classification. It is concluded that the exfoliative technique is a tool combined with the evaluation of morphological changes and can identify malignancies early.